A survey on the positive mass theorem for asymptotically flat initial data sets - Huang, Lan-Hsuan (Comptes Rendus. Mécanique)
In honor of Yvonne Choquet-Bruhat’s 100th birthday, we present this survey on the positive mass theorem. Originating from a conjecture in general relativity regarding the ADM mass, the positive mass theorem has significantly influenced geometry and analysis over the past four decades and continued to inspire new connections. We review seminal contributions as well as recent advances, and then we focus our discussions on the equality case and the counter-examples arising from pp-wave spacetimes.